Tonometry in keratoconus - V.V. Averich; A.V. Volzhanin (РМЖ "Клиническая офтальмология")
V.V. Averich, A.V. Volzhanin Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation Measurement of intraocular pressure (IOP) in keratoconus is associated with significant difficulties. Thus, because of corneal protrusion and changes in its biomechanics, the most common method of IOP measurement, applanation tonometry, provides significant error. The emergence of novel methods that are less dependent on corneal biomechanics has partially eliminated this error. These methods include tonometry based on new principles and dynamic contour tonometry. One of the "gold standards" for IOP measurement is Goldmann tonometry. Most foreign studies compare Goldman tonometry and one or more of the above-mentioned novel methods. However, in keratoconus, Goldman tonometry underestimates the IOP level and is therefore non-informative. Few studies compare IOP measurements and Maklakov tonometry. Finally, very few studies have compared IOP measurements at various stages of keratoconus, and their results are controversial. Comparing tonometry at different stages of keratoconus and studying fundamental changes in the hydrodynamics in keratoconus are relevant tasks in ophthalmology today. Keywords: cornea, keratoconus, tonometry, intraocular pressure, hydrodynamics, gold standard. For citation: Averich V.V., Volzhanin A.V. Tonometry in keratoconus. Russian Journal of Clinical Ophthalmology. 2024;24(1):36–40 (in Russ.). DOI: 10.32364/2311-7729-2024-24-1-7.